Health Equity in an Age-Friendly Health System: Identifying Potential Care Gaps. Issue 11 (10th March 2022) - Morgan, Emily; De Lima, Bryanna; Pleet, Anna; Eckstrom, Elizabeth
Abstract: Background: The Age-Friendly Health Systems (AFHS) initiative uses a 4Ms framework—What Matters, Mentation, Medication, and Mobility—to encourage patient-centered care for older adults. Many health systems have implemented the core elements of AFHS with the goal to uniformly apply them to all patients 65 years and older. However, equity in AFHS delivery has not yet been examined. Methods: Five health equity factors—gender, race, ethnicity, preferred language, and electronic patient portal (MyChart) activation—were cross-sectionally analyzed against the 4Ms framework for patients in an academic internal medicine clinic seen between April 2020 and April 2021 ( N = 3 370). Bivariate analysis and multiple logistic regression models analyzed the relationship of health equity variables to the 4Ms metrics and were represented with odds ratios and 95% confidence intervals. Results: Preferred language, gender, and MyChart activation yielded significant 4M metric pairings. Females were 1.22 times more likely than males, and English-speaking patients were 2.27 times more likely than non-English-speaking patients to receive advance care planning ( p < .01). Females and patients with MyChart activation were about 2 times more likely to have a high-risk medication on their medication list compared to males and patients without MyChart activation ( p < .01). Patients with MyChart activation were 2.08 times more likely than patients without MyChart activation to get cognitive screening ( p < .001). Conclusion: This study, the first to incorporate demographic data into AFHS outcomes, suggests a need to develop best practices for equitable Age-Friendly care at the clinical team and institutional policy levels.